HYBRID BATTERY-LESS LED DRIVER MENGGUNAKAN BOOST CONVERTER BERBASIS KONTROL PROPOSIONAL - M. Syafiuddin (POLITEKNIK NEGERI BENGKALIS, 2019)
The Government policy about energy management based on regulations of the Minister of Energy and Mineral Resources number 13 and 14 on 2012 concern saving of electricity use and energy management as a form of utilizing energy resources effectively, efficiently, and rationally, without reducing building functions should be an energy audit. So LED Driver is made in this prototype to utilize energy from photovoltaic without batteries for building lighting in the daytime, so besides saving in terms of load (LED) it is also saving energy sources. This paper will discuss LED drivers using photovoltaic (PV). The use of hybrid battery-less led drivers in this paper to increase the rate of savings electricity usage in buildings. Led drivers have the hybrid designed that can replace the PV power supply to the PLN power supply when the power generated by PV is less than nominal power. The output voltage of the LED is controlled by STM32F1 microcontroller using a boost converter. Experimental results in the field voltage generated by the LED driver is 195 Vdc. The power produced by the LED driver is 100 watts using 4 LED. And the value of the efficiency of the Boost converter reaches 92%.